Draft Annual Plan 2005-06 (Text) Government of Madhya Pradesh - Planning Commission (Planning Commission, 2005)
Development of the social sector along with technology absorption in agriculture and industry, which are the principal sectors of our economy, is nowadays considered as the primary objective of any economic development efforts. In Madhya Pradesh the development programmes have been carefully implemented during the five-year plan periods. However, the objective of enhancing the quality of life of people has not been fully achieved so far. This annual plan aims to reduce poverty substantially and to bring the state at par with the other developed states. This is sought to be done through all round development of manpower and human -resources required for socio economic development in the state, enhancement in the level of agricultural and industrial production, execution of comprehensive antipoverty programmes and employment generation.
Government of Madhya Pradesh, Planning, Economics and Statistics Department